Metode dan Corak Penafsiran al-Qur’an - Ghilman Nursidin Syarief (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2019)
Text of the Qur'an which is a revelation from Allah Subhanahu Wa Ta’ala. is the main source of Islamic law which must be understood by all Muslims. Understanding the understanding of the text or verse of the Qur'an is very dependent on the knowledge of the person who reads it. In this case the commentators have a tendency that is different from one another. This makes the works of interpreters also have different styles. This paper seeks to provide an explanation of some interpretive features, starting from the history of the emergence and interpreters and their interpretations. This is expected to make it easier to get to know the Qur'an based on the style of interpretation.